1980
DOI: 10.3109/01480548009002221
|View full text |Cite
|
Sign up to set email alerts
|

Acute oral toxicity of Selected Flavour Chemicals

Abstract: The acute oral lethal doses are reported in rats or mice for 63 substances which are used in flavorings. For specific groups of compounds which contain several representatives of one structural class, some effects of structure on acute oral toxicity were observed. For pyrazines, the addition and position of methyl groups affected the toxicity while the substitution of ethyl for methyl had little effect. Toxicity increased with the proximity of the methyl group. The thiazoles and thiazolines tested had similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…105 An approximate oral LD 50 value ranging between 800 and 1600 mg/kg was found in mice treated with DPTS. 106 Some disulfides, in particular DMDS and DPDS, have been shown to cause mild to severe red blood cell hemolysis in cats, dogs, and a variety of livestock animals following oral ingestion. 57,107,108 Vegetables, particularly onions and onion oil, containing relatively high amounts of these and other disulfides have long been associated with hemolytic anemia following accidental or intentional ingestion by dogs and farm animals.…”
Section: International Journal Of Toxicology 33(supplement 1)mentioning
confidence: 99%
“…105 An approximate oral LD 50 value ranging between 800 and 1600 mg/kg was found in mice treated with DPTS. 106 Some disulfides, in particular DMDS and DPDS, have been shown to cause mild to severe red blood cell hemolysis in cats, dogs, and a variety of livestock animals following oral ingestion. 57,107,108 Vegetables, particularly onions and onion oil, containing relatively high amounts of these and other disulfides have long been associated with hemolytic anemia following accidental or intentional ingestion by dogs and farm animals.…”
Section: International Journal Of Toxicology 33(supplement 1)mentioning
confidence: 99%
“…3-(Decyloxy)-2-hydroxy-1-propanesulfonic acid (18) and 2-myristynoyl pantetheine (24), which contain sulfur atoms and appeared only in sulfur-fumigated samples, might be the transformation products of the sulfur fumigation. Moreover, the volatile oil might be oxidised during sulfur fumigation, which may explain the oxygen atom in some of the newly appeared compounds [α-lonone (19), For the toxicities of the constituents of volatile oil, it was reported that the LD 50 of 2-amylfuran (5) on mouse by oral is 1200 mg/kg (Moran et al 1980). Phenylethyl alcohol (11) is not a developmental toxicity hazard for humans (Politano et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The supporting substances are listed in brackets. (Moran et al, 1980) (6-Pentyl-2H-pyran-2-one [10.031]) Rat M, F Gavage 1600 -5000 (Piccirillo & Hartman, 1980a) (Mixture of 5-Hydroxy-2-decenoic acid delta-lactone, 5-Hydroxy-2-dodecenoic acid delta-lactone, and 5-Hydroxy-2-tetradecenoic acid deltalactone ) Rat M, F Gavage 3363 (Reagan & Becci, 1984a) (Dodec-6-eno-1,4-lactone [10.009]) Rat M, F Oral > 5000 (Watanabe & Morimoto, 1990a) Rat NR Oral > 5000 (Wohl, 1974a) (3,7-Dimethyloctano-1,6-lactone [10.027]) Rat M, F Gavage > 5000 (Lewis & Palanker, 1979a) (5-Hexyl-5-methyldihydrofuran-2(3H)-one [10.051]) Rat NR Oral > 5000 (Moreno, 1976j) Flavouring Group Evaluation 10 Revision1 (FGE.10 Rev1)…”
Section: Annex Iv: Toxicitymentioning
confidence: 99%